PERALIHAN HAK ATAS MILIK KENDARAAN BERMOTOR DIBAWAH TANGAN DALAM JAMINAN FIDUSIA (STUDI DI KOTA BATAM) - NURLAILY NURLAILY (PREMISE LAW JURNAL, 2016)
Finance Corporate is one of the containers has a trend that is in demand by the public in possession of a motor vehicle today. With the rampant growth of these finance companies, then provide a wide range of selection options for prospective customers to use the services of a Finance Corporate. For example: a comparison of interest rates, flexible terms, and the rapid process of disbursement of funds to finance the vehicle of interest by the potential consumers into a particular reason for consumers in determining believed Financing Company. Vehicles purchased by consumers with the help of funding from finance companies, of course, legally set in Law No. 42 of 1999 on Fiduciary written stipulates that vehicles purchased in installments, to be charged Fiduciary. But with the passing of culture in society regarding the purchase of a motor vehicle with a loading fiduciary, causes people to have ideas that are more economical and efficiency in the process of transfer of the motor vehicle to the other party (the debtor second), namely by way of a purchase agreement under hand without reporting to the Finance Corporate. Keywords : Finance Corporate